Code-Switching in Multilingual Societies: Significance, Patterns, Functions, and Sociolinguistic Implications - Mustafayeva, Laya Abdurahim; Akbarova, Flora Samandar; Gurbanova, Gulnara Korkhmaz; Abdullayev, Afgan Ali; Muradova, Gultaj Huseyn; Ahmadova, Vafa Shamil; Aliyeva, Konul Ramig; Aghamirza, Dilara Hamidova; Hajiyeva, Aytan Fikrat; Aynur, Garayeva; Nazirzada, Leyla Nazir (Forum for Linguistic Studies, 2025)
This study examines the phenomenon of code-switching within multilingual societies, emphasizing its patterns, communicative functions, and sociolinguistic implications. This study utilizes data gathered from various multilingual communities, specifically in India, Nigeria, and the United States. It employs both qualitative and quantitative methodologies to investigate the factors and motivations behind language switching among speakers. The results indicate that code-switching functions as both a linguistic mechanism and a social practice, intricately connected to aspects of identity, power relations, and cultural representation. Additionally, Multilingual communities serve as rich environments for linguistic innovation, characterized by the dynamic and intricate interactions of languages rather than their segregation into distinct categories. In these contexts, code-switching transcends its function as a simple linguistic mechanism; it serves as a significant process for the construction of identity, the negotiation of social dynamics, and the creation of meaning. In the contemporary context characterized by globalization, the prevalence of multilingualism has transitioned from a peripheral occurrence to a significant aspect of societal dynamics. The prevailing perspective has shifted significantly, moving away from simplistic interpretations towards more nuanced understandings that acknowledge code-switching as a complex and regulated linguistic phenomenon. The findings indicate notable patterns in both inter-sentential and intra-sentential switching, while also proposing potential implications for educational policies, digital communication, and sociolinguistic theory.